Rhizosphere Bacteria From Panax notoginseng Against Meloidogyne hapla by Rapid Colonization and Mediated Resistance - Wu, Wentao; Wang, Jingjing; Wang, Zhuhua; Guo, Liwei; Zhu, Shusheng; Zhu, Youyong; Wang, Yang; He, Xiahong (Frontiers in Microbiology, 2022)
The root-knot nematodes (RKNs) are soil-borne pathogens that severely affect panax notoginseng growth and productivity. Thus, there is an urgent need for biological control agents or green nematicides to control the root-knot nematodes. Rhizosphere bacteria can effectively control RKNs through different mechanisms. In this study, the three rhizosphere Bacillus strains, isolated from the root of P. notoginseng, were evaluated the nematicidal activity and biological control efficacy against root-knot nematodes. In addition, we also evaluated the colonization ability of the two bacteria strains with significant biocontrol effect and dynamic regulation of genes related to systemic resistance in P. notoginseng. The rhizosphere Bacillus velezensis GJ-7 and Bacillus cereus NS-2 showed high nematicidal activity against M. hapla in vitro and significantly reduced the number of root galls in three different control experiments. The results of colonization experiments showed that the strain GJ-7 and NS-2 colonized panax notoginseng root rapidly and stably. Additionally, the colonization of strain NS-2 and GJ-7 activated the defense-responsive genes in panax notoginseng. These results indicated that the B. cereus strain NS-2 and B. velezensis strain GJ-7 have the potential of successful ecological niche occupation and enhance plant resistance, therefore could be considered as a potential biocontrol agent against root-knot nematodes.